2012
DOI: 10.1007/s12264-012-1057-5
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 activation as a bifurcation point between plasticity and cell death

Abstract: As death mediating proteases caspases and caspase-3 in particular, have been implicated in neurodegenerative processes, aging and Alzheimer’s disease (AD). However, emerging evidence suggests that in addition to their classical role in cell death caspases have a key role in modulating synaptic function. It is remarkable that active caspases-3 which can trigger widespread damage and degeneration, aggregates in structures as delicate as synapses and persists in neurons without causing acute cell death. Here we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
141
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(153 citation statements)
references
References 75 publications
8
141
1
3
Order By: Relevance
“…The activation of caspase-3 has been identified in various types of cells observed with apoptosis (38). Caspase-3 was previously revealed as a downstream molecule of the Bcl-2 family (37).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of caspase-3 has been identified in various types of cells observed with apoptosis (38). Caspase-3 was previously revealed as a downstream molecule of the Bcl-2 family (37).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of caspase-3 is a key and common event of two major apoptosis signaling pathways, mitochondrial pathway and death receptor pathway (Mazumder et al, 2008;Snigdha et al, 2012). The death receptor pathway activates initiator caspase-8 and then cleaves its downstream effector caspases, such as caspase-3 which transducts the apoptosis signal, while the mitochondrial pathway is initiated by the mitochondrial dysfunction and then causes activation of caspase-9 which triggers caspase-3 activation (Fulda et al, 2006).…”
Section: Knockdown Of Med19 Enhances Chemo-sensitivity To Cisplamentioning
confidence: 99%
“…Caspase-3 (CASP3), which we find in this study to be decreased in synaptosomal fractions of morphine treated animals, is best known for its role during apoptosis as an executioner caspase that leads to neuronal cell death (58,59). However, recent studies have revealed not only developmental functions but also a functional role for this enzyme in the regulation of synaptic plasticity, learning, and memory (60). Studies have demonstrated the presence of caspase-3 in both dendrites and PSD fractions (61), and have shown that it can modulate synaptic transmission by interacting with and cleaving specific AMPA subunits at the PSD (62), and by regulating the internalization of synaptic AMPA receptors (63).…”
Section: Discussionmentioning
confidence: 58%